Etnis Tionghoa di Kabupaten Ciamis: Diaspora dan Dinamika Permukimannya pada Abad ke-19 Hingga Pertengahan Abad ke-20 - Desril Riva Shanti; Wulandari Retnaningtiyas; Indri Nur Sa’adah; Oerip Bramantyo Boedi; Reni Guyuna Sari (PURBAWIDYA: Jurnal Penelitian dan Pengembangan Arkeologi, 2022)
Discussions and studies on Chinese settlement (Chinatown) in the eastern hinterland of West Java are still scarce. Historical data about the region formerly known as East Priangan shows an indication of the existence the ethnic community, including in Ciamis Regency. The diaspora of ethnic Chinese to the area, their interactions with the surrounding community, and the forming of ethnic community which later developed into a settlement with all the physical aspects attached to it are the issues to be answered. This study uses historical-archeology approach with initial observations on existing archaeological remains and interviews with several informant to determine the spatial and temporal scope. The result showed that the Chinese settlement in Ciamis Regency consist of various elements such as residential buildings, socio-cultural and educational facilities, buildings for spiritual activities, burial complex, and industrial area that were developed in accordance with varying background conditions. It can also be said that one of the reasons on the arrival of ethnic Chinese in Ciamis Regency is correlated to the opening of plantations in East Priangan. Initially, their role tends to be the ‘middle-man’ between natives and Europeans. However, during the later period they also gave contribution and significance in various fields, be it social, cultural, economic, or political.